Film criticism in the context of the formation of a new aesthetic experience in the early 1920s - Sayenkova-Melnickaya, Lyudmila P. (Journal of the Belarusian State University. Journalism, 2023)
The object of this research is the formation of film criticism experience in newspaper and magazine periodicals of the early 1920s. It was the time of the formation of a new aesthetics, understanding the artistic potential of cinema, the search for forms of presentation of the first screen art form in the media. The purpose of the study is to identify the peculiarities of the influence of aesthetic theories of the beginning of the 20th century on film critical discourse as a special area of journalism, to determine the approaches in film criticism to the representation of the artistic integrity of a film work. The aesthetic potential of film criticism as a part of journalism from a historical perspective is comprehended in scientific discourse for the first time. The practical significance of the results of the presented scientific work lies in understanding the culture-forming function of film criticism and increasing the degree of demand for this type of creative activity in the media environment.